Copper-Catalyzed N-tert-Butylation of Aromatic Amines under Mild Conditions Using tert-Butyl 2,2,2-Trichloroacetimidate - Cran, John W.; Vidhani, Dinesh V.; Krafft, Marie E. (Synlett, 2014)
A variety of aromatic amines have been found to expediently undergo copper-catalyzed N-tert-butylation in the presence of tert-butyl 2,2,2-trichloroactimidate at room temperature.
Keywords: anilines; tert-butylation; copper; catalysis; alkylation